PERENCANAAN BANGUNAN PENAHAN SEDIMEN (CHECK DAM II) DI DAERAH ALIRAN SUNGAI CILIMAN DESA LEUWIKOPO, KECAMATAN GUNUNGKENCANA, KABUPATEN LEBAK - Wawan Handayani; Gunawan Noor2 Noor; Muhammad Taufik Rido Taufik Rido (Journal of Sustainable Civil Engineering (JOSCE), 2019)
Sediment-retaining buildings are transverse river structures that function to prevent sedimentation so that the riverbed does not occur due to erosion and large flow speeds. The Ciliman River Basin (DAS) in the Dam has been irrelevant at the time of initial planning, so it needs to be reviewed by analyzing the stability of the Leuwikopo sediment-retaining weir by using a flood discharge of fifty years (Q50), with design discharge 413,537 m3 / second. This research was conducted to find out whether the stability of the Ciliman sediment-retaining weir is safe for the forces acting with (Q25). 383,979 m3 /second. The calculated forces are their own gravity, earthquake force, lift force, water gravity, water pressure and weir stability analysis that are taken into account are the hydraulic gradient, eccentricity, bearing capacity, rolling force and shear force. The weir dimensions are safe for eccentricity, soil carrying capacity, bolster force, shear force and forces that work both at normal water level conditions and flood water